Perancangan Logo Dalam Branding Panti Asuhan (International Forum of Researchers and Lecturers, 2024)
The logo serves as a visual representation encapsulating the essence and unique characteristics of the orphanage, creating a first impression that can shape a positive perception of the institution. More than just a personal expression, the importance lies in the observer's perception and response, making it the primary focus in the visual communication design process. The success of a design is determined by its ability to effectively communicate ideas, stories, or information to the observer or targeted audience. Therefore, alignment between the intended message and the observer's perspective and understanding becomes the key to success in visual communication design. With a well-crafted design, the logo can establish an emotional connection with stakeholders, build trust, and enhance the appeal of the orphanage in the eyes of the public.